Thermodilution-derived resting coronary flow measurement: "a reverse dose finding study". (25th November 2020) - Gallinoro, E; Colaiori, I; Di Gioia, G; Fournier, S; Kodeboina, M; Candreva, A; Sonck, J; Pijls, N.H.J; Collet, C; De Bruyne, B
Abstract: Background: Hyperemic absolute coronary blood flow (in mL/min) can be safely and reproducibly measured with intracoronary continuous thermodilution of saline at room temperature at an infusion rate of 20 mL/min. This study aims at assessing the best infusion rate to measure resting flow by thermodilution, i.e. low enough to avoid microvascular dilation but high enough to allow reliable thermodilution tracings Methods and results: In 26 coronary arteries (24 patients) with angiographic non-significant stenoses, absolute flow was assessed by continuous saline thermodilution at infusion rates of 10 mL/min and 20 mL/min using a pressure/temperature sensored guide wire, a dedicated infusion catheter and a dedicated software. Average peak velocity (APV) was measured simultaneously using an intracoronary Doppler-wire. In addition, in a subgroup of 10 arteries, absolute flow and APV were also measured during saline infusion at 6 ml/min and 8 ml/min. In 26 coronary arteries there was no significance difference in the Pd/Pa and in the APV at baseline and during the infusion of saline at 10 ml/min (Pd/Pa: 0.94±0.057 vs 0.94±0.059, p=0.82; APV: 22.2±8.40 vs 23.2±8.39 cm/s, p=0.63). In contrast, at an infusion rate of 20 mL/min, we observed a significant decrease in Pd/Pa compared to baseline (0.85±0.089 vs 0.95±0.053 vs, respectively, p<0.001) and a significant increase in APV (22.2±8.4 cm/s to 57.8±25.5 cm/s, respectively, p<0.001). The coronary flow reserve (CFR) evaluated by Doppler and intracoronary continuous thermodilution correlated well (r=0.87, 95% CI = 0.72–0.94, p<0.001) and Bland-Altman analysis documented a mean bias of −0.003 (limit of agreement −1.05 to 1.04) thus indicating the presence of resting coronary blood flow during the infusion of 10 mL/min of saline. In 10 coronary arteries saline infusions at 6 and 8 ml/min did not produce any significant changes in the Pd/Pa and in the APV compared to baseline and both Doppler and Thermodilution derived CFR correlated well at each infusion rate (6 ml/min: r=0.71, 95% CI 0.14–0.92, p=0.02; 8ml/min: r=0.78, 95% CI=0.31–0.95, p=0.007). However, with an infusion rate of 6 mL/min, an unstable thermodilution tracing was observed. Accordingly, Bland-Altman analysis showed a significantly larger dispersion of the CFR values when 6 ml/min was used to measure resting coronary flow (as compared with 8 m/min): mean bias at 6 ml/min: −0.53, limits of agreement: −2.25 to 1.20: mean bias at 8 ml/min: 0.004, limits of agreement: −0.72 to 0.73. Conclusion: Absolute resting coronary flow can be measured by intracoronary continuous thermodilution of saline at infusion rate of 8–10 ml/min. Funding Acknowledgement: Type of funding source: None